O-028 The LUNA aneurysm embolization system for treatment of intracranial aneurysms. (4th July 2012) - Piotin, M; Sourour, N; Biondi, A; Mounayer, C; Blanc, R
Abstract : Purpose: The LUNA Aneurysm Embolization System (AES) is a self-expanding ovoid device that serves as an intra saccular flow diverter as well as a scaffold for endothelization across the neck. The objective of this prospective clinical study was to evaluate the ability of the AES to occlude intracranial aneurysms while maintaining patency of the parent artery. Materials and Methods: 15 patients with intracranial aneurysms were enrolled (intention to treat) in the study so far. Immediate post-implantation occlusion grade (complete (complete obliteration of the aneurysm including the neck), near-complete (persistence of any portion of the original defect of the arterial wall), or incomplete (any opacification of the sac) compared to baseline), and parent vessel compromise were evaluated. Patients underwent neurological and neurocognitive testing with the Modified Rankin Scale and the National Institute of Health Stroke Scale (NIHSS) at baseline and time of discharge. Follow-up included clinical assessment at 1 month and 3 months, clinical and angiographic follow-up at 6 months. Results: 15 patients (14 women, 1 man) with 14 unruptured and 1 ruptured saccular aneurysms (5 para-ophtalmic, 3 AcoA, 3 ICA-Pcom, 2 MCA, 1 ICA bifurcation, 1 A1; sizes from 5.0 to 6.7 mm) were enrolled to date in the study. In all but 1 aneurysm (1 failed procedure converted in coiling immediately after aneurysm dome perforation with the microcatheter of a recently ruptured aneurysm) 1 AES was deployed per aneurysm. In four cases, the AES embolization was carried out with balloon microcatheter assistance. In one case, the AES failed to detach and was exchanged for a second AES device that detached. In one case, AES placement led to aneurysm perforation that was controlled by temporary balloon occlusion and heparin reversion. In one case, thrombo-embolic complication was treated with i.a. injection of Abciximab. Immediate complete occlusion was obtained in one case, near complete occlusion was obtained in nine cases, no occlusion in four cases. Clinical follow-up was uneventful. To date, four patients with four aneurysms were followed with angiography at 6 months, showing complete occlusion in two cases, neck remnants in two cases. There was no parent artery stenosis or occlusion. Conclusion: Preliminary results demonstrate good safety profile. The first short-term angiographic follow-up are promising. More and longer follow-up are pending. Competing interests: None.